PENERAPAN OUTSOURCING DI LEMBAGA KONSERVASI BALI ZOO - Eva Yunita, Ni Putu; Markeling, I Ketut; Dedy Priyanto, I Made (Kertha Semaya : Journal Ilmu Hukum, 2013)
Theme of this writing is application of outsourcing in Bali Zoo Institute for Conservation of Gianyar regency, it aims to determine the application of outsourcing in Bali Zoo Institute for Conservation of Gianyar regency. Within this writing, the method that used is empirical legal research that examines the application / implementation of the statutory provisions on the practice field. The conclusion that can be drawn is that the application of outsourcing in Bali Zoo Conservation Society is not in accordance with the provisions of the law as it applied in the field of animal keeper which is a main job and it can not be applied to the outsourcing.
Keywords: Implementation, Outsourcing, Conservation Institute, Bali Zoo